Anti-Drunk Driver Pedal Lock and Carbon Monoxide Alarm using Gas Sensor Detection - Zahirudin, Amir Ridhwan; Ali, Siti Hajar Aminah (Evolution in Electrical and Electronic Engineering, 2022)
Drinking alcohol is not a good habit and will give side effects on health, some people still choose to drink because they need a mechanism to relieve stress and to forget their bad days when things do not happen as planned. Drinking and driving are essentially referred to as drunk driving and are one of the deadliest things in life for any alcohol user. Over the eight-year period from 2011 to 2018, 1,147 individuals died as a result of drunk driving accidents in Malaysia. Besides that, the number of automobiles and parking spots is growing and in 2018, new registrations of motor vehicles increased by 8.2% to 1,218,662 compared to 1,125,900 in 2017. Therefore, when the number of cars increases, the long exposure to carbon monoxide (CO) could occur. This could lead to confusion, vomiting and nausea. The main objectives are to design a breathalyzer to detect the drunk driver and to develop a pedal lock for the car system to prevent drunkards from driving with an additional feature of CO detection in the car with the application of notification. The method used is by detecting the presence of alcohol and CO with MQ3 and MQ7 sensors and transmitting data to Blynk for notification purposes. We obtained the data from the sensor via Arduino IDE and analyzed it by using Matlab R2020b. Comparisons are made and evaluated the overall performance and the system. The graph outcome that we obtained shows the level of concentration, effectiveness and accuracy of the system. It can be concluded that the system is able to determine the condition of the driver and the car before it can be driven. For future development, a GPS system could include in this implementation because it could help the user locate themselves accurately for locating purposes.